In Vitro Germination and Initial Seedling Development of Krantz Aloe by Smoke-saturated Water and Seed Imbibition - Claudia A. Espinosa-Leal; Silverio Garcia-Lara (HortTechnology, 2020)
Krantz aloe (Aloe arborescens) is one of two aloe species currently used for the extraction of active ingredients that can be useful in the cosmetic and pharmaceutical industries. However, krantz aloe plants have been frequently collected from the wild, which is threatening wild populations. In vitro tissue culture would allow the growth of krantz aloe under controlled conditions, optimizing the production of active ingredients without risk to wild populations. The establishment of cultures from krantz aloe plant explants has proved difficult as a result of the long response times of the explants and their release of polyphenols. Krantz aloe seeds are not commonly used as a means of propagation because of their low germination percentages. The objective of this study was to evaluate the effects of seed imbibition (SI) with water and the addition of smoke-saturated water (SSW) to the culture medium on the in vitro germination and initial seedling development of krantz aloe. Seeds were germinated in vitro in axenic conditions. The treatments used were the addition of 10% SSW to the culture media, SI, and a combination of both (10% SSW + SI). Daily germination was recorded and gross morphology was measured after 1 month of culture establishment. The maximum germination percentage (GP) was achieved when 10% SSW was in the medium (97.2%), followed by the combined application of 10% SSW + SI (96.6%), both of which were almost 30% greater and significantly different from that of the control (69.4%). SI had an 83.3% GP. No significant differences were observed among treatments in any of the observed development parameters (leaf and root length and number). Taken together, these findings show that the use of SSW improves the in vitro germination of krantz aloe without affecting seedling development, indicating preliminarily that SSW represents a useful in vitro germination promoter for this species.